Erosion reduces soil microbial diversity, network complexity and multifunctionality - Qiu, Liping; Zhang, Qian; Zhu, Hansong; Reich, Peter B.; Banerjee, Samiran; van der Heijden, Marcel G. A.; Sadowsky, Michael J.; Ishii, Satoshi; Jia, Xiaoxu; Shao, Mingan; Liu, Baoyuan; Jiao, Huan; et al. (The ISME Journal, 2021)
While soil erosion drives land degradation, the impact of erosion on soil microbial communities and multiple soil functions remains unclear. This hinders our ability to assess the true impact of erosion on soil ecosystem services and our ability to restore eroded environments. Here we examined the effect of erosion on microbial communities at two sites with contrasting soil texture and climates. Eroded plots had lower microbial network complexity, fewer microbial taxa, and fewer associations among microbial taxa, relative to non-eroded plots. Soil erosion also shifted microbial community composition, with decreased relative abundances of dominant phyla such as Proteobacteria, Bacteroidetes, and Gemmatimonadetes. In contrast, erosion led to an increase in the relative abundances of some bacterial families involved in N cycling, such as Acetobacteraceae and Beijerinckiaceae. Changes in microbiota characteristics were strongly related with erosion-induced changes in soil multifunctionality. Together, these results demonstrate that soil erosion has a significant negative impact on soil microbial diversity and functionality.